Compressed Air Generator for Low Wind Speed Electrification - Veerapol Monyakul, Varin Vongmanee (Naresuan University Journal: Science and Technology (NUJST); Vol 21 No 3 (2013): September-December 2013, 2014)
The objective of this paper is to present a compressed air generator (CAG) that designs for low wind speed electrification application. The CAG is a reciprocating machine operated with low pressure of compressed air that works as an expansion air engine. It transforms the compressed air power to the electrical power via the expansion air engine coupling with an induction machine for electrification. The CAG is not like the conventional machine, which use the fuel fossil for internal combustion, therefore, it don’t generate air pollution that is the main problem in environment. The CAG prototype is designed with the local contents in THAILAND, which consists of four cylinders operating alternatively with air pressurize. The engine is modified from standard TOYOTA engine and controlled by an electronics controller unit, which produces the on-off control signal for solenoid valves as the charging-discharging valves to supply the air pressurize to machine. The experimental result shows the system design, investigates the characteristic of CAG prototype and presents all of machine efficiency. The system was tested under a range of expansion pressure ratios in order to determine its characteristics and performance. At the operational pressure of 5 bar, the efficiency of expansion air of 49.34% is calculated, while the efficiency of generator of 60.85% is examined. The overall efficiency of system of approximately 30% is also investigated. Keywords: Compressed Air Generator, Expansion Air Engine, Compressed Air Energy, Compressed Air Electrification, Wind Energy.
Keywords: Compressed Air Generator, Expansion Air Engine, Compressed Air Energy, Compressed Air Electrification, Wind Energy.